MULTIMEDIA IN SCHOOL PRACTICE - PIECUCH, Aleksander (Trends in education, 2008)
This article make entrance to contemplation of knowledge and certain of use multimedia orders from Podkarpackie province teachers, to help teaching process. On account of limited volume this article, in elaboration showed quantitative results of research some threads large research problematic.
Keywords: media; mass communications; multimedia